Effect of Light Intensity on Initial Survival of Fat Snook (Centropomus parallelus, Pisces: Centropomidae) Larvae - Vinicius Ronzani Cerqueira; André Macedo Brügger (Brazilian Archives of Biology and Technology, 2001)
Different light intensities were tested during the larval rearing of fat snook (Centropomus parallelus) to evaluate its influence on survival and functional swim bladder rate. Newly-hatched larvae were obtained by stripping of hormonally induced broodstock, and were stocked in 32-liter tanks at densities from 30 to 50 L-1. Four experiments were carried out testing six light intensities: 50, 100, 200, 500, 1500, and 2500 lx, and total darkness as a control. Mean survival ranged from 0.06 to 16.0% and were significantly influenced by light intensity. Complete darkness resulted in 100% mortality after one week, larvae appeared to have starved since they had empty stomachs. The species has the characteristics of a visual-feeder. Survival was the highest at 200 lx, while at 500 lx was higher than at 50, 100, and 2500 lx. Frequency of functional swim bladder ranged from 36.8 to 100%, but it was not significantly correlated with light intensity. Based on this study, a medium light intensity, 200 to 1500 lx, is recommended for rearing fat snook larvae. Extreme values must be avoided, mainly in the first two weeks after hatching. Diferentes intensidades de luz foram testadas na larvicultura do robalo peva, Centropomus parallelus, avaliando sua influência na sobrevivência e insuflação da bexiga gasosa. Larvas obtidas de desova induzida foram mantidas até 14 dias, em tanques de 32 L, com densidade inicial de 30-50 L-1. Foram utilizados o escuro total e 6 intensidades de luz: 50, 100, 200, 500, 1.500 e 2.500 lx. A sobrevivência média variou entre 0,06 e 16,0%, dependendo significativamente (P<0,05) da intensidade de luz. No escuro, as larvas morreram após uma semana, sem conteúdo no tubo digestivo, comprovando serem predadores visuais. Em 200 lx, a sobrevivência foi maior que em 500, 1.500 e 2.500 lx. Em 500 lx também foi superior a 50, 100 e 2.500 lx. A insuflação da bexiga gasosa ficou entre 36,8 e 100%, independendo da intensidade de luz. Recomenda-se intensidade luminosa média, de 200 a 1.500 lx, evitando valores extremos, sobretudo nas duas primeiras semanas de vida.